Prevention is better than cure - the art of avoiding non-adherence to antiretroviral treatment - Leith Kwaan; Gurpreet Kindra; Lulama Mdutyana; Anna Coutsoudis (AOSIS, 2010)
The much-used phrase 'prevention is better than cure' is applicable to many circumstances, including human immunodeficiency virus (HIV) infection. In recent years suggestions have been made for a move towards treatment strategies that emphasise prevention of foreseeable adherence problems on a patient-by-patient basis, through focused patient preparation before commencing antiretroviral therapy (ART). This is well elucidated in a statement made in 2004 by Coetzee et al.:1 'As it is difficult to ascertain robust predictors of adherence, there has been a move to concentrate on patient preparation before the initiation of ART rather than the use of non-clinical predictors of adherence or selection criteria. A paradigm focused on preparation rather than selection is better suited to the aggressive targets for the scaling up of ART in countries with large epidemics (such as in South Africa), where the view of ART as a very expensive rationed intervention is rapidly changing.'